It is a binomial expression with one variable, m.
Chat with our AI personalities
3m + 9 = 36subtract 9 from both sides3m = 27divide both sides by 3m = 27/3 = 9
To solve the equation 5m + 3 = 3m + 9, you need to isolate the variable m. Start by subtracting 3m from both sides to get 2m + 3 = 9. Then, subtract 3 from both sides to get 2m = 6. Finally, divide by 2 to find m = 3.
9m + 9m + 3m + 3m = 24m
3
If -3m+5=-22, then you do this math: -22-5= -3m. -22-5=-27, so if you take the negative signs away from -27 and -3m, divide 27 by 3 to get 9, therefore m=9.